Organic Waste Chopper Tool Design Using Autodesk Inventor 2015 Software - Nengah Ludra Antara (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
In the program of mechanical engineering, the software used to draw is Autodesk Inventor. Autodesk inventor is a CAD program in the program of engineering that is applied to the design of mechanics in 3D. In designing a tool, of course, it is preceded by a planned design concept. In making a design a tool requires a process or steps for making the design. These steps include the size, dimensions, and materials used in making organic waste chopper tool. The drawing process uses the 2015 Autodesk Inventor program, the first is the making of sketches, components on the machine, followed by assembly of each component, then rendering images, animation as the final stages of drawing design input into